ChemInform Abstract: Site‐Selective Acylations with Tailor‐Made Catalysts. Issue 31 (14th July 2016) - Huber, Florian; Kirsch, Stefan F.
Abstract: A concept that aims at tailor‐made catalysts for the site‐specific acylation of alcohols is described.